2001
DOI: 10.1007/s002440010209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heavy Metal Concentrations in Tissues of Red Foxes from Adjacent Urban, Suburban, and Rural Areas

Abstract: The red fox (Vulpes vulpes) is a representative of the canid family with wide distribution in the Northern Hemisphere and Australia. The increasing utilization of urbanized habitats by red foxes prompted us to test whether this species may be used to monitor the presence of anthropogenic pollutants in cities or suburbs. For that purpose, we compared the concentrations of heavy metals (Cd, Pb, Cu, Zn) in foxes from urban, suburban, and rural areas within the municipality of Zürich (Switzerland). The kidney and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…It has a high position in the trophic pyramid and accumulates various xenobiotics, including Hg. Taking into account our results and findings of other authors, it may be argued that the fox exhibits a measurable response to environmental Hg pollution and meets the requirements for bioindicators [23, 24, 42, 48, 52, 53]. Thanks to the collection of data on the mercury concentration in fox liver and kidney, it is possible to make comparisons not only between European countries but entire continents (e.g.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has a high position in the trophic pyramid and accumulates various xenobiotics, including Hg. Taking into account our results and findings of other authors, it may be argued that the fox exhibits a measurable response to environmental Hg pollution and meets the requirements for bioindicators [23, 24, 42, 48, 52, 53]. Thanks to the collection of data on the mercury concentration in fox liver and kidney, it is possible to make comparisons not only between European countries but entire continents (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…Among mammals, primarily herbivorous ungulates are deemed good indicators of pollution: fallow deer Dama dama (L., 1758), red deer Cervus elaphus (L., 1758), moose Alces alces (L., 1758) and the omnivorous wild boar Sus scrofa (L., 1758), but they are not represented outside their natural habitats and areas of incidence [3741]. Furthermore, the home ranges of the individuals of those species are very large, which hinders the determination of sources of pollution [42]. In contrast to the aforementioned ungulates, the fox easily adapts to a wide range of environments, including urban areas, and occupies small territories with an average home range of 0.5 km 2 [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has a large geographical range, but not too large home range; its local populations are stable; it has a permanent position in the food chain; it is relatively easy to determine its age and it is also game, so it is not difficult to obtain. For these reasons, it is sometimes used in studies on different types of environmental pollution (Corsolini et al 1999; Dip et al 2001; Kalisińska et al 2009). Currently, pollution with anthropogenic substances, including F − , is so widespread that there is a reasonable need to determine concentrations in common mammals living in the vicinity of man, including the red fox.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, relatively little is understood about these processes in wild terrestrial mammals of the Arctic (Dehn et al 2006; Gamberg et al 2005). Studies have shown a correlation of THg concentrations among various tissues (Cumbie 1975; Dip et al 2001; Kalisinska et al 2009; Piskorova et al 2003; Wren 1986). Muscle, liver and kidney are often used as bioindicators to assess biological variation among cohorts, individuals, and populations (Alonso et al 2004; Becker and Wise 2006; Brookens et al 2008; Gutleb et al 1998; McGrew et al 2013; Yamamoto et al 1987).…”
Section: Introductionmentioning
confidence: 98%